REGIMES OF MEANING AND INTERACTION IN O CASARAO DA RUA DO ROSARIO, BY MENALTON BRAFF - Ribeiro Santos, Flavia Karla [UNESP]; Duarte, Renata Cristina (Univ Antioquia, Dept Linguistica & Literatura, 2021)
We examine how conservative and progressive values emerge in Menalton Braff's O Casarao da Rua do Rosario as the characters interact with each other and with the world built by literary language,using the theoretical-methodological reference of French semiotics,. We focus on the feelings resulted from the oppression of a conservative matriarch with rigid moral and religious values and by the political regime in force in Brazil from 1964 until 1985. The analysis reveals the conflictive interaction between the matriarch and her younger sister, who, together with her children, rejects the conservative figured by the house they live.
Keywords: contemporary Brazilian literature; Menalton Braff; political and social oppression; regimes of meaning and interaction; French semiotics